Dilemas políticos sobre los movimientos sociales. El accionar colectivo de los sectores populares en el Chile de los años ochenta - Zamorano Farías, Raúl (Revista Mexicana de Sociología, 2024)
This study contains a theoretical analysis of the ways in which social theory conceptualized the collective action of popular sectors and the impact of these interpretations on the political process of the transition to democracy during the 1980s and the early 1990s in Santiago, Chile. A review of the two major paradigms to explain the type and characteristics of the new social movements; one aimed at the mobilization of resources, the other oriented towards identity, permits the reconstruction of the scenario and the theoretical discussion accompanying the emergence of the so-called New Social Movements (NMS) in Latin America in general and Chile in particular.